Legal positions of the Constitutional Court of Ukraine: main signs and definition - Romana Reva (Проблеми Законності, 2016)
The practice of a single body of constitutional jurisdiction indicates on the necessity of a certain number of amendments to the current Law of Ukraine “On the Constitutional Court of Ukraine”. It is impossible to achieve the quality regulation of these issues without a thorough scientific analysis of basic features of the legal positions of the Constitutional Court of Ukraine.